Gallbladder cancer: clinic, diagnosis and treatment: about 175 observations - Estefan, Alberto; Melogno, Silvio; Portos, Ruben (Cirugía del Uruguay, 1973)
A hundred and seventy-five cases of gall baldder cancers treated at the University Hospital (Hospital de Clínicas) in the period 1954-1971, are analyzed. Gall bladder cancer is discussed, including clinical aspects, diagnosis and treatment. The paper includes a summary of literature on this subject. Recent advances in its ireatment and the opinion of severa! authors on controversia! aspects are included. In the light of present knowledge and results obtained, the author indicates radical surgical treai;ment in cases of gall bladder cancer.